An ombudsman ACT – a resolution to maladministration amongst public servants in Malaysia / Azlina Mohd Hussain, Dr. Muhamad Helmi Muhamad Khair and Dr. Nor Syamaliah Ngah - Mohd Hussain, Azlina; Muhamad Khair, Muhamad Helmi; Ngah, Nor Syamaliah (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
The maladministration among public servants has long been an issue in Malaysia. How Malaysia used to combat it is through, inter alia, the Public Complaints Bureau (PCB). This article will look into the evolution of the PCB and why there has been a shift in perspective and a movement to pass an Ombudsman Act and establish an ombudsman office in Malaysia to address maladministration among civil servants in Malaysia.